A comprehensive review of two-phase anaerobic digestion for organic fraction of Municipal Solid Waste - Dhakal, Subash; Pallawi Sharma; Anish Ghimire; Bikash Adhikari; Bhola Thapa (Journal of Innovations in Engineering Education, 2024)
Managing municipal solid waste (MSW) is becoming a more pressing global issue that requires creative and long-lasting solutions due to population expansion and changing consumption habits. Given its capacity to transform organic waste into useful resources like biogas and fertilizers, anaerobic digestion (AD) presents a viable solution to the urgent problems related to waste management in this context. This study investigates the potential of AD, and more specifically the two-stage anaerobic digestion (TSAD) process, as a game-changing technique for the treatment of organic fraction municipal solid waste (OFMSW). The efficiency of TSAD is thoroughly examined in this study, which takes into account a number of variables including temperature, pH, solid retention time, hydraulic retention time, organic loading rate, and carbon to nitrogen ratio. Though TSAD is a promising approach, there is still a significant knowledge gap about its stability, ideal operating parameters, and widespread application, especially when it comes to MSW management. The study highlights the necessity for more investigation to close this knowledge gap and realize TSAD’s full promise for handling the difficulties involved in energy production and municipal waste treatment.